Second-Generation Hydrogel Coils for the Endovascular Treatment of Intracranial Aneurysms: A Randomized Controlled Trial. Issue 3 (March 2018) - Taschner, Christian A.; Chapot, René; Costalat, Vincent; Machi, Paolo; Courthéoux, Patrick; Barreau, Xavier; Berge, Jérôme; Pierot, Laurent; Kadziolka, Krzysztof; Jean, Betty; Blanc, Raphaël; Biondi, Alessandra; et al.
Abstract : Background and Purpose—: Endovascular embolization of intracranial aneurysms with hydrogel-coated coils lowers the risk of major recurrence, but technical limitations (coil stiffness and time restriction for placement) have prevented their wider clinical use. We aimed to assess the efficacy of softer, second-generation hydrogel coils. Methods—: A randomized controlled trial was conducted at 22 centers in France and Germany. Patients aged 18 to 75 years with untreated ruptured or unruptured intracranial aneurysms measuring 4 to 12 mm in diameter were eligible and randomized (1:1 using a web-based system, stratified by rupture status) to coiling with either second-generation hydrogel coils or bare platinum coils. Assist devices were allowed as clinically required. Independent imaging core laboratory was masked to allocation. Primary end point was a composite outcome measure including major aneurysm recurrence, aneurysm retreatment, morbidity that prevented angiographic controls, and any death during treatment and follow-up. Data were analyzed as randomized. Results—: Randomization began on October 15, 2009, and stopped on January 31, 2014, after 513 patients (hydrogel, n=256; bare platinum, n=257); 20 patients were excluded for missing informed consent and 9 for treatment-related criteria. Four hundred eighty-four patients (hydrogel, n=243; bare platinum, n=241) were included in the analysis; 208 (43%) were treated for ruptured aneurysms. Final end point data were available for 456 patients. Forty-five out of 226 (19.9%) patients in the hydrogel group and 66/230 (28.7%) in the control group had an unfavorable composite primary outcome, giving a statistically significant reduction in the proportion of an unfavorable composite primary outcome with hydrogel coils—adjusted for rupture status—of 8.4% (95% confidence interval, 0.5–16.2; P =0.036). Adverse and serious adverse events were evenly distributed between groups. Conclusions—: Our results suggest that endovascular coil embolization with second-generation hydrogel coils may reduce the rate of unfavorable outcome events in patients with small- and medium-sized intracranial aneurysms. Clinical Trial Registration—: URL:https://www.drks.de/drks_web/ . Unique identifier: DRKS00003132. Abstract : Supplemental Digital Content is available in the text.